2010
DOI: 10.1051/0004-6361/201014019
|View full text |Cite
|
Sign up to set email alerts
|

A coincidence between a hydrocarbon plasma absorption spectrum and theλ5450 DIB

Abstract: Aims. The aim of this work is to link the broad λ5450 diffuse interstellar band (DIB) to a laboratory spectrum recorded through expanding acetylene plasma. Methods. Cavity ring-down direct absorption spectra and astronomical observations of HD 183143 with the HERMES spectrograph on the Mercator Telescope on La Palma and the McKellar spectrograph on the DAO 1.2 m Telescope are compared. Results. In the 543-547 nm region a broad band is measured with a band maximum at 545 nm and FWHM of 1.03(0.1) nm coinciding w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
25
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 30 publications
2
25
0
Order By: Relevance
“…Despite decades of study into carbon chains, these have failed to conclusively account for the astronomical features (Maier et al 2004). Nevertheless, two recent matches between laboratory spectra and DIBs have been reported for the short carbon chains H 2 CCC and HCCCCH + ; however, these coincidences are still being debated (Linnartz et al 2010;Maier et al 2011b;Oka & McCall 2011;Krełowski et al 2011Krełowski et al , 2010. Indeed, after further scrutiny, HCCCCH + is now regarded as an unlikely carrier of a DIB due to mismatches in the band profile and central wavelength ).…”
Section: Introductionmentioning
confidence: 99%
“…Despite decades of study into carbon chains, these have failed to conclusively account for the astronomical features (Maier et al 2004). Nevertheless, two recent matches between laboratory spectra and DIBs have been reported for the short carbon chains H 2 CCC and HCCCCH + ; however, these coincidences are still being debated (Linnartz et al 2010;Maier et al 2011b;Oka & McCall 2011;Krełowski et al 2011Krełowski et al , 2010. Indeed, after further scrutiny, HCCCCH + is now regarded as an unlikely carrier of a DIB due to mismatches in the band profile and central wavelength ).…”
Section: Introductionmentioning
confidence: 99%
“…In the past two decades the field has converged towards larger carbonaceous molecules, like the fullerenes and polycyclic aromatic hydrocarbons (PAHs), which have electronic transitions in the optical (see for example Salama et al 1999;Ruiterkamp et al 2005;Kokkin & Schmidt 2006;Zhou et al 2006;and Salama et al 2011). New diffuse bands have been detected in one line-of-sight which appear to match with naphthalene and anthracene cations (Iglesias-Groth et al 2008 and the weak 5450 Å DIB is found to match with an absorption band arising from a hydrocarbon plasma created in the laboratory (Linnartz et al 2010). Linear-C 3 H 2 has been put forward as a carrier of the 5450 and 4881 Å DIBs Based on observations collected at the European Southern Observatory, Paranal, Chile .…”
Section: Introductionmentioning
confidence: 99%
“…Results for calculated transitions or inferred vibronic progressions of large molecules are promising but await further study and confirmation from lab experiments. This is also the case for the good comparison between a hydrocarbon plasma band and the 5449 DIB (Linnartz et al 2010 ) has been challenged by others, revealing inconsistencies between the observations and laboratory data (Oka & McCall, (2011), Krelowski (this volume)).…”
Section: Dib Carrier Candidatesmentioning
confidence: 94%